1984
DOI: 10.1128/iai.46.2.367-371.1984
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of experimental actinomycosis in mice by Eikenella corrodens

Abstract: The infectivity of Actinomyces israelii in a susceptible-weanling-mouse was increased by the presence of Eikenella corrodens in the inoculum. A minimal infecting dose of 1.7 X 10(7) CFU of A. israelii was required to establish chronic lesions after an intraperitoneal injection. When E. corrodens (3.8 X 10(7) CFU) was included in the inoculum, chronic lesions were established with a dose of 8.5 X 10(4) CFU of A. israelii. E. corrodens alone did not produce persistent lesions. Viable E. corrodens could be recove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The observation that very high numbers of Actitwtnyees organisms are needed to form persistent infections (3,17) is corroborated by our attempt to induce experimental infections in this study. But it is unlikely that such high numbers of these bacteria may gain entry into the periapical tissue from an infected root canal.…”
Section: Discussionsupporting
confidence: 74%
“…The observation that very high numbers of Actitwtnyees organisms are needed to form persistent infections (3,17) is corroborated by our attempt to induce experimental infections in this study. But it is unlikely that such high numbers of these bacteria may gain entry into the periapical tissue from an infected root canal.…”
Section: Discussionsupporting
confidence: 74%
“…The level of Eikenelia corrodens was signifi-cantly higher In progressing sites harboring A. actinomycetemcomilans than non-progressing sites harboring that species and suggests a possible synergism between these organisms (Table 4). A recent publication by Jordan et al (1984) had demonstrated enhancement of experimental actinomycosis in mice by either E. corrodens or A. actinomycelemcomitans. Within the medical literature, both A. actinomycetemcomilans and E. corrodens have been reported as interacting with other organisms to exaggerate an infectious process (Brill et at.…”
Section: Discussionmentioning
confidence: 99%
“…Jordan et al established experimental actinomycotic infections in mice and the histological evidence showed that polymorphonuclear leukocytes were not able to penetrate and invade the developing central bacterial granule of A. israelii lesions, which resulted in the “unreachable attack” of the leukocytes towards the bacteria inside the granule, while the existence of the inside bacteria would enhance the viability of Actinomyces cells by producing an anaerobic environment. Thus, the companion bacteria would be able to elaborate the toxins and enzymes as well as inhibiting host defenses to facilitate infections [ 46 ].…”
Section: Biological Functions Of Actinomyces Spmentioning
confidence: 99%